Investigation of transcutaneous electrical nerve stimulation improvements with microneedle array electrodes based on multiphysics simulation. (18th February 2020) - Soltanzadeh, Ramin; Afsharipour, Elnaz; Shafai, Cyrus
Abstract: This paper investigates microneedle array electrodes for transcutaneous electrical nerve stimulation, and compares their performance with conventional surface electrodes. A three‐dimensional model of tissue was developed for finite element multiphysics simulations. Investigations included current density in different depths of a tissue, space constant under electrodes, specific absorption ratio of tissue, selectivity of stimulation, temperature rise, and blood flow. Results showed that microneedle electrodes have up to 10% higher selectivity than the surface electrodes. Furthermore, it was found that stimulation using microneedle electrodes provides more robust current density at different tissue depths compared to the surface electrode stimulation. Microneedle electrodes showed enhanced stimulation parameters, particularly for targeting a specific nerve in a specific depth of a tissue. Abstract :